Neurofibromatosis type 1, fibromuscular dysplasia, and ischemic stroke: an association lost in time? A case report - Fonseca, Igor Oliveira Da [UNESP] (2023)
Neurofibromatosis Type 1 (NF1) is a rare cause of ischemic stroke (IS) in the general population. We report a case of a young patient with NF1 in whom IS was caused by fibromuscular dysplasia. An angiographic study demonstrated occlusion in the right internal carotid artery (ICA), just after its origin, and the left ICA, just before the intracranial portion, and brain magnetic resonance imaging showed the limits of an area of brain infarction in the right frontoparietal region. Despite these concomitant neuroimaging findings, this association is rare, and it is difficult to establish the contribution to the outcome made by each of these diseases, which treatment is the best to implement, or what prognosis is.